Relato de caso de um paciente com mucopolissacaridose tipo VI (Síndrome de Maroteaux-Lamy) - Kumagai, Eliane Tiemi (2010)
Mucopolysaccharidosis (MPSs) are inherited metabolic diseases caused by a deficiency of lysosomal enzymes responsible for degradation of glycosaminoglycans, resulting in accumulation of these macromolecules within the lysosomes of cells,resulting in dysfunction of various organs and tissues in a progressive manner. A variation of this disease is a mucopolysaccharidosis (MPS) type VI or Maroteax-Lamy syndrome, in which the patient appears normal at birth but, in addition to the accumulation of MPSs arise progressive deformities such as short stature, coarse face, contractures joint, several skeletal defects, as well as cardiovascular,hepatoesplenomigalia, ocular, oral and speech therapy. This type of MPS does not have mental retardation and psychomotor retardation. This report presents some consequences arising from the speech therapy and dental syndrome, a carrier male with eight years of age. Physical examinations were performed, radiographic, speech therapy, dental, medical history and also collected information in the records of APAE. In examining speech, neurovegetative functions presented with bilateral chewing movements with anteroposterior and tongue. Presented short oral breathing (abdominal and thoracic), breathless and noisy. At the oral clinical examination,showed anterior open bite, macroglossia, tongue, but was not detected the presence of dental caries. In panoramic radiography, it was detected without the formation of five permanent teeth and images consistent with dentigerous cyst in the lower molars. Changes in stomatognathic systems and functions are prevalent in individuals with MPS type VI and these findings suggest that dental treatment and speech therapy has an important role in the quality of life of these individuals.